2018
DOI: 10.1007/s41871-018-0008-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Innovative Dynamic Cutting Force Modelling in Micro-milling and Its Experimental Validation

Abstract: In this paper, an innovative cutting force modelling concept is presented by modelling cutting forces against micro-cutting processes such as micro-milling, ultraprecision turning and abrasive micromachining, and also taking account of microcutting dynamics. The modelling represents the underlying micro-cutting mechanics and physics in micro-milling in an innovative multi-scale manner, i.e. the specific cutting force at the unit length, unit area and unit volume by considering the size effect, cutting fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Micro-milling raises significant issues when removing material at the microscale owing to the effect of scaling, otherwise known as size effect. It has been shown that the size effect modifies the mechanism of material removal in conventional milling [ 55 , 56 ]. However, the characterization and exact cause of this effect remain a point of contention among researchers, indicating that many factors influence chip formation and material removal mechanisms at the microscale.…”
Section: Fundamentals Of the Processmentioning
confidence: 99%
“…Micro-milling raises significant issues when removing material at the microscale owing to the effect of scaling, otherwise known as size effect. It has been shown that the size effect modifies the mechanism of material removal in conventional milling [ 55 , 56 ]. However, the characterization and exact cause of this effect remain a point of contention among researchers, indicating that many factors influence chip formation and material removal mechanisms at the microscale.…”
Section: Fundamentals Of the Processmentioning
confidence: 99%
“…As a result, the predicted chip thickness, that significantly affects the dynamic cutting forces, needs to be further modified by considering the tool run-out. 1416 In order to accurately predict the dynamic cutting forces, a novel instantaneous chip thickness algorithm is integrated to determine the real chip thickness, tool position and tool tip trajectory by taking account of the effects of the micro-tool geometry change resulted from the tool run-out.…”
Section: Analytical Chip Thicknessmentioning
confidence: 99%
“…They also investigated the influences on the machined surface profile of the spindle vibration. Cheng and colleagues 4,5 proposed an innovative dynamic cutting force model that considered instantaneous chip thickness and revealed the relationship between process dynamics and micro-cutting mechanics. Lu et al 6 adopted a transfer matrix method to establish a multi-rigid-flexible-body dynamics model of an ultra-precision fly-cutting machine tool, and he concluded that the stiffness of the aerostatic bearing spindle has a significant influence on the surface.…”
Section: Introductionmentioning
confidence: 99%